Riding the Rhythm of Melatonin Through Pregnancy to Deliver on Time - McCarthy, Ronald; Jungheim, Emily S.; Fay, Justin C.; Bates, Keenan; Herzog, Erik D.; England, Sarah K. (Frontiers in Endocrinology, 2019)
Pregnancy is influenced by the circadian (“circa” or approximately; diēm or day) system, which coordinates physiology and behavior with predictable daily changes in the environment such as light/dark cycles. For example, most species deliver around a particular time of day. In mammals, circadian rhythms are controlled by the master circadian pacemaker, the suprachiasmatic nucleus. One key way that the suprachiasmatic nucleus coordinates circadian rhythms throughout the body is by regulating production of the sleep-promoting hormone melatonin. Serum melatonin concentration, which peaks at night and is suppressed during the day, is one of the best biological indicators of circadian timing. Circadian misalignment causes maternal disturbances in the temporal organization of many physiological processes including melatonin synthesis, and these disturbances of the circadian system have been linked to an increased risk for pregnancy complications. Here, we review evidence that melatonin helps regulate the maternal and fetal circadian systems and the timing of birth. Finally, we discuss the potential for melatonin-based therapeutic strategies to alleviate poor pregnancy outcomes such as preeclampsia and preterm birth.